2014
DOI: 10.13189/cor.2014.020101
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lens Culinaris Agglutinin-Reactive Fraction of Alpha Fetoprotein as an Early Diagnostic Marker for Hepatocellular Carcinoma among Sudanese Patients with Chronic Liver Disease

Abstract: Hepatocellular carcinoma (HCC) is a common complication in patients with chronic viral hepatitis and liver cirrhosis. Detection of HCC at an early stage is critical for a favorable clinical outcome. This is a case-control, hospital-based study, aimed to determine the usefulness of Lens Culinaris Agglutinin-Reactive Fraction of Alpha Fetoprotein (AFP-L3) as an early diagnostic marker for HCC in Sudanese Patients with chronic liver diseases. Blood samples were collected from 25 patients with HCC, 32 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
0
1
Order By: Relevance
“…From a gender perspective, AFP levels above 400 ng/ml belonged to male patients, and normal AFP levels below 20 ng/ml belonged to the majority of female patients. This was contradictory to the research from Shata et al, (2014) who found that there was no difference in AFP levels between men and women (Shata, et al, 2014).…”
Section: Discussioncontrasting
confidence: 66%
“…From a gender perspective, AFP levels above 400 ng/ml belonged to male patients, and normal AFP levels below 20 ng/ml belonged to the majority of female patients. This was contradictory to the research from Shata et al, (2014) who found that there was no difference in AFP levels between men and women (Shata, et al, 2014).…”
Section: Discussioncontrasting
confidence: 66%